Technological Innovations and the Allocation of Decision-Making Authorities in Swiss Firms - Kathrin Armbruster (University of Basel, Center of Business and Economics (WWZ), 2011)
Since several decades, information and communication technologies (ICT) as well as new organizational designs change the working life in firms. Using nationally representative Swiss firm-level panel data, the present paper analyzes the relationship between these developments and examines, whether ICT is associated with centralization or decentralization tendencies. The results suggest a positive impact of ICT on the degree of delegation. Furthermore, the diffusion of ICT use within the workforce and the intensity of ICT investments are essential for the decentralization effect of ICT. Thus, reduced agency costs owing to ICT use result in decentralized decision-making authorities in Swiss firms. The results are robust to potential endogeneity biases like reversed causality and unobserved firm characteristics.
Keywords: 330; Informationstechnik; Organisatorischer Wandel; Dezentrale Organisation; Unternehmensorganisation; Schweiz